EL USO DE LOS BIENES INCAUTADOS POR DELITOS DE ENRIQUECIMIENTO ILÍCITO Y SU FINALIDAD SOCIAL - Muñoz Guarnizo, Juan Pablo (2020)
This thesis is the final report of the investigation process, motivated in the second paragraph of Art. 279 of the Organic Comprehensive Penal Code stipulates: It will be understood that there was Illicit Enrichment not only when the patrimony has been increased with money, things or goods, but also when debts have been canceled or extinguished obligations and in turn in the last referendum on February 4, 2018, Ecuador approved the sanction of all persons convicted of acts of corruption with the loss of their property, for which I believe indispensable what, After their seizure, they must be used by the Ministry of Economic and Social Inclusion for the benefit of the common good of the people who require it through community service works such as: hospitals, citizen security, schools, day-care centers, centers and health subcenters, rehabilitation centers for people with problems of alcoholism and drug addiction, and other social purposes. It contains conceptual references and doctrinal elements that allow the understanding of the legal problems and what as a result of this investigative process, allowed me to formulate as a legal proposal the reform of the Comprehensive Organic Criminal Code in this sense.